The efficiency and effectiveness of marking methods on spatially heterogeneous forest treatments - Cadry, Jeff, author; Smith, Frederick, advisor; Dickinson, Yvette, advisor; Cottrell, Stuart, committee member; Mackes, Kurt, committee member (Colorado State University. Libraries, 2015)
Fire suppression, historic grazing, past logging, and climate change have resulted in increased tree densities and fuel loads, greater forest homogeneity, and large, uncharacteristic wildfires in the lower montane forests of Colorado's Front Range. The Pike and Arapahoe-Roosevelt National Forests are currently restoring forest structure through the implementation of forest thinning. Historically these forests were more heterogeneous with individual trees, groups of trees varying in quantity, and openings. The silvicultural prescriptions required for these restoration treatments are complex, and foresters are experiencing difficulties conveying these complex prescriptions to the contractors implementing the treatments. The forest service has used three different marking methods to implement this prescription: individual tree marking (ITM), designation by prescription (DxP), and designation by description (DxD). The objective of this study was to investigate the effectiveness and efficiency of these marking methods. A combination of quantitative and qualitative methods were used to address the objective. The quantitative methods investigated the heterogeneity of pre- and post-treatment forest structures at eight sites within the lower montane zone of the Colorado Front Range. The qualitative methods investigated the facilitators and constraints among stakeholders with respect to marking methods. These methods were implemented by conducting semi-structured interviews with stakeholders (n=10) who were involved in the treatments being analyzed in the quantitative portion. The results of the quantitative portion indicated that each of the three marking methods created more heterogeneity than the control (traditional fuels treatment). The marking method creating the largest increase in heterogeneity depended on the metric that was being utilized. This was a result of the scales of measurement being different for each of the metrics. With each marking method creating heterogeneity, marking method selection criteria should be utilized to choose the most appropriate marking method. The qualitative analysis identified selection criteria in the following categories: experience of the stakeholders, marking vs. designation, DxP vs DxD, and hybrid marking methods. These categories should be considered when selecting a marking method for a spatially heterogeneous treatment.